Hierarchically parallel coupled finite strain multiscale solver for modeling heterogeneous layers. (15th August 2014) - Mosby, Matthew; Matouš, Karel
Summary: We develop a three‐dimensional, hierarchically parallel, finite strain multiscale solver capable of computing nonlinear multiscale solutions with over 1 billion finite elements and over 574 million nonlinear equations on 1552 computing cores. In the vein of FE 2, we use the nested iterative procedure and devote the solver to multiscale cohesive modeling of heterogeneous hyperelastic layers. The hierarchically parallel multiscale solver takes advantage of a client‐server non‐blocking communication matrix that limits latency, starvation, and overhead by overlaying computations at different scales. We perform simulations of real‐scale engineering devices and bridge O ( 1 0 6 ) in length‐scales, spanning from O ( 1 0 1 )  mm to O ( 1 0 1 )  nm in spatial resolution. Verification of the hierarchically parallel solver is provided together with a mesh convergence study. Moreover, we report on the scaling performance. Copyright © 2014 John Wiley & Sons, Ltd.